Appetitive aggression is associated with lateralized activation in nucleus accumbens. (January 2022) - Schöne, Maria; Seidenbecher, Stephanie; Kaufmann, Jörn; Antonucci, Linda Antonella; Frodl, Thomas; Koutsouleris, Nikolaos; Schiltz, Kolja; Bogerts, Bernhard
Highlights: Unclear neurobiological correlates of appetitive aggression in non-clinical samples. Applying functional magnet resonance imaging during visual violence perception. Affinity towards hedonistic violence relates to lateralized accumbens activation. Different processing of appetitive aggression in the two hemispheres. Abstract: Aggression can have a hedonistic aspect in predisposed individuals labeled as appetitive aggression. The present study investigates the neurobiological correlates of this appetitive type of aggression in non-clinical samples from community. Applying functional magnet resonance imaging (fMRI), we tested whether 20 martial artists compared to 26 controls had a higher activation in the nucleus accumbens (NAcc), a central part of the dopaminergic, mesolimbic reward system. Subjects had to watch violent vs. neutral pictures representing appetitive aggression. The affinity towards hedonistic violence was assessed by the Appetitive and Facilitative Aggression Scale (AFAS). Furthermore, the subjects rated all the pictures with regard to how pleasant and violent they were. The martial artists reported a higher AFAS-score and a more positive perception of violent pictures. On the neural level, across all subjects, there was a significant positive correlation between the AFAS-score and the activation in the left NAcc and an inverse association with the activation of the right NAcc when watching violent compared to neutral pictures. This lateralization effect indicates a different processing of hedonistic aspects of aggression in the two hemispheres.